To a question of the principles of criminal proceedings - Kuanaliyeva G.A. (Хабаршы. Заң сериясы, 2016)
In this article the author considered the principles of the criminal procedure right as procedural guarantees of the rights and legitimate interests of the personality in criminal trial. The principles express essence and the content of criminal trial, characterize its most important properties and qualitative lines, a subject and a method of procedural regulation. The addressee they have the person and the citizen and the appropriate government bodies. The bodies of the state conducting process have to act on the basis of the established principles and bear all consequences connected with their violation.